PDTM-10. USE OF A NOVEL, HAND-HELD, ELECTRONIC DNA ANALYSIS PLATFORM TO QUANTIFY MULTI-GENE MOLECULAR RESPONSE IN CSF OF PATIENTS WITH HIGH-GRADE GLIOMA. (11th November 2019) - Bruzek, Amy; Tunkle, Leo; Babila, Clarissa; Muruganand, Ashwath; Stallard, Stefanie; Thamilselvan, Veena; Qin, Tingting; Wolfe, Ian; Mody, Rajen; Robertson, Patricia; Maher, Cormac; Muraszko, Karin; et al.
Abstract: BACKGROUND: For midline tumors, surgical biopsy risks neurological injury. Non-invasive methods for diagnosis and surveillance are greatly needed. Tumors release DNA into cerebrospinal fluid (CSF-ctDNA), allowing for potential detection and serial monitoring of tumor-associated genetic mutations by CSF sampling. Current detection platforms are limited by their requirement for assay development for each mutation (digital droplet PCR), or cost and timeliness (Illumina sequencing). We hypothesized that direct, electronic analysis of CSF-ctDNA with a novel, hand-held platform (Oxford Nanopore MinION) could provide real-time, ultra-deep sequencing of patient-specific alterations in CSF-ctDNA. METHODS: We established multiple clinical trials for pediatric high-grade glioma with required multi-time point (0, 2, and 6 month) correlate lumbar puncture (LP) at time of MRI, with accrual ongoing. We performed amplicon-based PCR on CSF-ctDNA for recurrent mutations and sequenced patient samples (tumor tissue n=8, tumor CSF n=60) and normal controls (tissue n=5, CSF n=24) using NanoPore technology. Variant allele fractions (VAF) were determined via MinKNOW, Guppy, MiniMap2, and Integrated Genome Browser. RESULTS: Sensitivity was 79% and specificity 100% by NanoPore. Time from LP to results was 12 hours. A 17-year-old female presented with a biopsy-proven grade IV thalamic glioma with clonal mutations in H3F3A K27M, PIK3CA E545G, TP53 R158G, and TP53 R248Q. After failing standard treatment, she was enrolled in the ONC201 clinical trial and underwent serial LPs. MRI showed stable tumor at 2 months and 40% decrease at 6 months of treatment. H3K27M VAF increased from baseline at 2 months, but decreased to 1% at 6 months of treatment, results that were confirmed by ddPCR. PIK3CA E545G, TP53 R158G, and TP53 R248Q demonstrated the same decrease in VAF, with p-value of < 0.0001. CONCLUSIONS: We demonstrate a rapid, reliable method to detect tumor mutations in CSF, and further show molecular remission of H3K27M glioma by CSF sampling.